2014
DOI: 10.5585/conssaude.v13n3.4894
|View full text |Cite
|
Sign up to set email alerts
|

Resultados de um programa de cessação tabagística: análise de novos procedimentos

Abstract: Introdução: O tabagismo pode ser tratado com eficácia por terapias com enfoque na abordagem cognitivo-comportamental, sendo imprescindível a descrição minuciosa desta. Objetivo: Descrever um programa de cessação tabagística com novos procedimentos e avaliar seu índice de sucesso. Métodos: Participantes de um programa de cessação tabagística, baseado em terapias cognitivas comportamentais e farmacológicas, foram acompanhados por um ano, e a taxa de cessação avaliada foi, no mínimo, de seis meses, após pararem d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
(24 reference statements)
0
5
0
8
Order By: Relevance
“…25 Regarding the hemodynamic behavior, the passive smoking group presented higher systolic blood pressure values compared with the smoking group (P ϭ .02). Although the average values were considered normal, 13 these data become alarming when considering that previous studies 26,27 have shown that people exposed to cigarette smoke have higher chances of developing hypertension. In addition, the sample in the present study Data are expressed as mean Ϯ SD and as median (interquartile range).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…25 Regarding the hemodynamic behavior, the passive smoking group presented higher systolic blood pressure values compared with the smoking group (P ϭ .02). Although the average values were considered normal, 13 these data become alarming when considering that previous studies 26,27 have shown that people exposed to cigarette smoke have higher chances of developing hypertension. In addition, the sample in the present study Data are expressed as mean Ϯ SD and as median (interquartile range).…”
Section: Discussionmentioning
confidence: 97%
“…This cross-sectional study evaluated 120 individuals, determined by sample size calculation (using a saccharin transit time test, with 80% test power and 95% confidence using an SD of 5.7, with a difference to be detected of 4, the sample calculation resulted in 32 individuals for each group), divided into 3 groups: 44 smokers enrolled in a smoking cessation program 13 at the University of São Paulo, Brazil; 38 passive smokers exposed to cigarette smoke daily (family of the smokers group); and 38 volunteers in the control group, recruited for the study. The study was conducted from March 2013 to July 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Os indivíduos tabagistas foram recrutados do programa de orientação e conscientização antitabagismo da UNESP de Presidente Prudente [13]. O grupo de não tabagistas foi formado por voluntários, estudantes e funcionários da UNESP de Presidente Prudente, que preenchiam os critérios de inclusão definidos previamente e que aceitaram realizar o protocolo proposto, tendo sido recrutados aleatoriamente pelos pesquisadores/autores da pesquisa.…”
Section: População E Amostraunclassified
“…It corresponds to a serious public health problem, since it represents a severe risk factor for cancer, cardiovascular diseases, respiratory diseases, and other health problems 2,3 . In addition, tobacco consumption has a direct effect on quality of life 4 .…”
Section: Introductionmentioning
confidence: 99%